Changes in Caco-2 cells transcriptome profiles upon exposure to gold nanoparticles. Issue 2 (4th March 2015) - Bajak, Edyta; Fabbri, Marco; Ponti, Jessica; Gioria, Sabrina; Ojea-Jiménez, Isaac; Collotta, Angelo; Mariani, Valentina; Gilliland, Douglas; Rossi, François; Gribaldo, Laura
Highlights: Biological effects (toxicity, uptake and changes in gene expression patterns) on Caco-2 cells of citrate-stabilized 5 nm and 30 nm AuNPs were compared. Exposure to 5 nm AuNPs had much stronger effect on gene expression as compared to treatment with 30 nm AuNPs. Nrf2 signaling stress response was among the highly activated pathways. Abstract: Higher efficacy and safety of nano gold therapeutics require examination of cellular responses to gold nanoparticles (AuNPs). In this work we compared cellular uptake, cytotoxicity and RNA expression patterns induced in Caco-2 cells exposed to AuNP (5 and 30 nm). Cellular internalization was dose and time-dependent for both AuNPs. The toxicity was observed by colony forming efficiency (CFE) and not by Trypan blue assay, and exclusively for 5 nm AuNPs, starting at the concentration of 200 μM (24 and 72 h of exposure). The most pronounced changes in gene expression (Agilent microarrays) were detected at 72 h (300 μM) of exposure to AuNPs (5 nm). The biological processes affected by smaller AuNPs were: RNA/zinc ion/transition metal ion binding (decreased), cadmium/copper ion binding and glutathione metabolism (increased). Some Nrf2 responsive genes (several metallothioneins, HMOX, G6PD, OSGIN1 and GPX2) were highly up regulated. Members of the selenoproteins were also differentially expressed. Our findings indicate that exposure to high concentration of AuNPs (5 nm) induces metal exposure, oxidative stress signaling pathways, and might influence selenium homeostasis. Some of detected cellular responses might be explored as potential enhancers of anti-cancer properties of AuNPs based nanomedicines.